Penerapan Pendidikan Multikultural dalam Pembelajaran Sejarah Islam di Prodi Pendidikan Sejarah Universitas Islam Sumatera Utara - Abdillah, Muhammad Fajar; Nababan, Surya Aymanda; Rahmat, Doris (Medan Resource Center, 2023)
The implementation of multicultural education in the teaching of Islamic history in the History Education Study Program at UISU (Universitas Islam Sumatera Utara) holds significant value and benefits. In this context, multicultural education aims to develop a comprehensive understanding of Islamic history in an inclusive manner, promote appreciation for cultural and religious diversity, and enhance students' cross-cultural communication skills and understanding. Through the implementation of multicultural education, students in the History Education Study Program at UISU can develop broader and deeper perspectives on Islamic history, including its influence on various regions and eras' cultures and societies. They can study and analyze the roles and contributions of different ethnic groups, languages, and traditions in the development of Islam. The multicultural education approach also enables students to understand that Islam has rich internal diversity, encompassing diverse worship practices, intellectual traditions, and theological thoughts. This research adopts a qualitative research method with a phenomenological approach, which involves critically analyzing social phenomena. The phenomenological approach is employed by the researcher to ensure the objectivity and scientific nature of the research. The researcher acts as a key instrument and suspends preconceived assumptions or biases. Meanwhile, qualitative methods can be used to uncover and understand the underlying aspects of phenomena, providing insights into the unknown or little-known aspects for both researchers and lecturers.